(untitled) (Bioresearch Communications, 2024)
Dengue is a mosquito-borne viral disease caused by four serotypes of the dengue virus (DENV-1, DENV-2, DENV-3, and DENV-4), which has impacted human populations for decades in tropical and subtropical regions, including Bangladesh. Understanding the genetic variability and mutation patterns of DENV-2 and DENV-3 is critical for developing effective control strategies, as these serotypes are more prevalent in Bangladesh. The E/NS1 gene junction, which comprises less than 3% of the DENV genome, is a recognized hotspot for mutation. In this study, 56 E/NS1 junction sequences of DENV-2 from 36 countries, including Bangladesh, were analyzed in silico. The Bangladeshi sequences were compared with the DENV-2 prototype strain (New Guinea C) and sequences from other countries. Analysis of Bangladeshi DENV-2 isolates revealed only one amino acid substitution (isoleucine to valine at position 742, I742V), caused by a nucleotide change (ATT to GTC). Phylogenetic analysis placed all Bangladeshi DENV-2 isolates within the Cosmopolitan genotype. Similarly, 35 E/NS1 junction sequences of DENV-3 from 19 countries, including Bangladesh, were analyzed. Sequences from Bangladesh obtained in 2002 (eight isolates) and 2020 (two isolates) were compared with the DENV-3 prototype strain (Philippines H87). The 2020 isolates exhibited two common amino acid substitutions (A759V and V769A), while the 2002 isolates showed three substitutions (S727G, A759V, and V769T). Phylogenetic analysis revealed a genotypic shift in Bangladeshi DENV-3 isolates, with 2002 isolates belonging to Genotype II and 2020 isolates classified as Genotype I. Envelope protein modeling for both DENV-2 and DENV-3 Bangladeshi isolates, compared to their respective prototype strains, revealed no significant structural changes in the E protein. However, protein stability analysis, based on changes in free energy due to amino acid substitutions, indicated a potential impact on the stability of the mutant E proteins compared to the prototypes. Further studies are needed to explore the clinical implications of these mutations. Bioresearch Commu. 11(1): 1749-1763, 2025 (January)